Emission‐Tunable Room‐Temperature Phosphorescent Polymers Based on Dynamic Reversible Supramolecule‐Mediated Photocrosslinking. Issue 1 (28th October 2021) - Lin, Xiaohan; Xu, Qingyang; Ma, Xiang
Abstract: Pure organic room‐temperature phosphorescence (RTP) materials can be used in optoelectronics, biochemical equipment, sensors and biological imaging. In the past few years, dynamic covalent chemistry has attracted significant attention because it provides a new way to produce intelligent optical materials with feedback functions. Two polymers are synthesized through supramolecular‐mediated [4+4] photocyclodimerization of anthracene, which can be reversibly transformed by photoreversible dynamic covalent bonds. The polymers show decent phosphorescence emission with different colors at room temperature, achieving the conversion between blue phosphorescence and cyan phosphorescence. This study provides a novel method for designing and synthesizing pure organic RTP materials with tunable emissions through dynamic covalent bonds. Abstract : In this work, a simple method is developed to achieve efficient room‐temperature phosphorescence (RTP) in the amorphous solid state. The effect of emission‐tunability is achieved by introducing photo‐reversible dynamic covalent bond into pure organic RTP polymers. This innovative method could expand the application of intelligent optical materials in the future.